The coupled lattice Boltzmann simulation of free convection in a finned L-shaped cavity filled with nanofluid. Issue 3 (10th October 2019) - Zhang, Peng; Ashraf, Muhammad Aqeel; Liu, Zhenling; Peng, Wan-Xi; Ross, David
Abstract : Purpose: This paper aims to investigate the free convection, heat transfer and entropy generation numerically and experientially. A numerical/experimental investigation is carried out to investigate the free convection hydrodynamically/thermally and entropy generation. Design/methodology/approach: The coupled lattice Boltzmann method is used as a numerical approach which keeps the significant advantages of standard lattice Boltzmann method with better numerical stability. On the other hand, the thermal conductivity and dynamic viscosity are measured using modern devices in the laboratory. Findings: Some correlations based on the temperature at different nanofluid concentration are derived and used in the numerical simulations. In this regard, the results will be accurate with respect to using theoretical properties of nanofluid, and close agreements will be detected between present results and the previous numerical and experimental works. The numerical investigation is done under the effect of Rayleigh number (103 < Ra < 106), volume concentration of nanofluid (?? = 0.5, 1, 1.5, 2, 2.5 and 3%) and thermal configuration of the cavity (Cases A, B, C and D). Originality/value: The originality of the present work lies in coupling of the lattice Boltzmann method with experimental observations to analyse the free convection in a cavity.